Topical Latanoprost (Pgf2u Analogue) For The Prevention Of Immediate Increase In Intraocular Pressure After Cataract Extraction - Nik Zaid, Nik Azlan (2001)
The effect of prostaglandin analogue PGF2a. was tested in immediate post-operative cataract extraction eyes. Seventy-two eyes undergoing endocapsular cataract extraction with capsular bag intraocular lens implantation using viscoelastic substance were randomly assigned into two groups. Thirty-six eyes in latanoprost group received 0.0050/0 latanoprost eye drop at the end of the operative procedure while another thirty-six eyes in control group received a topical drop of placebo (tetrahydrozoline hydrochloride) similarly. In all other respects the eyes were treated identically. Intraocular pressure (lOP) was measured preoperatively and at 3,6, 9 and 24 hours post-operatively. Pre-operatively the mean intraocular pressure was 12.31 ± 2.11 mmHg in the latanoprost group and 12.72 ± 2.49 mmHg in the control group. The mean lOP post-operatively was persistently higher than the pre-operative levels in both groups. An initial rise in mean lOP was noted at 6 hours post-operatively (from 17.75 to 21.80 mmHg). Subsequently, the mean lOP drops with the lowest post-operative lOP was noted at 24 hours post-operatively. Similar pattern of lOP changes were a1so seen in latanoprost group, however the mean lOP levels were always lower than lOP level in control group (from 15.94 to 19.11 mmHg). The highest mean post-operative lOP was 21.80 ± 7.32 mmHg. recorded in the control group at 6 hours post-operatively. The differences in the mean pressures in the two groups at corresponding times were not statistically significant (J> > 0.05).